Arithmetic Dice Media as Counting Concept Introduction for Early Childhood - Rohmah, Naili; Waluyo, Edi (Universitas Negeri Semarang, 2014)
Counting is one of mathematics branches that studies about operation, such as addition, subtraction, multiplication, and division. Arithmetic dice is a dice that is used for counting game. The purpose of this study is to know that Dice Arithmetic is beneficial as an introduction of counting concept for early childhood. This study employed an experimental method with pretest-posttest control group design. The subjects were children aged 5-6 years. The sample was taken using Purposive random sampling. The result of this study is that there was a significant influence on children when they were introduced to the concept of counting with Arithmetic Dice, compared to children who were introduced the concept of counting by conventional methods or worksheet. Arithmetic dice has principles like a six-sided dice. Each side of the dice is given a picture that can be assembled and the theme of the picture is customized based on the current theme. This study used two dice. Every child played two dice that had been prepared by the teacher. After the dice numbers appeared, the teacher directly asked the children some questions for example what the sum of the two numbers was, which number was bigger from the two dice, what the symbol of the number was.How to citeRohmah, N., & Waluyo, E. (2014). Arithmetic Dice Media as Counting Concept Introduction for Early Childhood. Indonesian Journal Of Early Childhood Education Studies, 3(2), 127-133. doi:10.15294/ijeces.v3i2.9486